Differential IL 10 serum production between an arm-based and a leg-based maximal resistance test. (February 2020) - Aragón-Vela, J.; Casuso, R.A.; Casals, C.; Plaza-Díaz, J.; Fontana, L.; Huertas, J.R.
Highlights: Elevated serum levels of IL10 were detected in the arm-based exercise. Both exercises induced similar IL6 and TNFα serum levels. The arm-based resistance test induced a higher muscular damage than the leg-based test. Abstract: Bench press (i.e. arm-based) and half-squat (i.e. leg-based) are exercises commonly used to increase and evaluate muscular strength. In addition to differences in the location of the muscles that participate in each exercise, the total muscle mass required for the latter is larger than that involved in the former. The aim of this study is to analyze the effects of a maximal incremental strength test when performed by bench press and by half-squat on myocellular damage, oxidative damage and the inflammatory cytokine response. Ten male athletes were subjected to half-squat and bench press incremental strength tests. Blood samples were collected at rest, 15-minutes and 24 h post-test. Hydroperoxide and malondialdehyde concentrations were determined as lipid peroxidation markers. Lactate dehydrogenase (LDH) and creatine kinase isoenzyme MB (CK-MB) activities were determined as markers of muscle damage. α-Actin concentration was determined as a marker of sarcomeric damage. Serum interleukin (IL) 6, IL10, and tumor necrosis factor alpha (TNFα) were determined to assess the inflammatory response. LDH and CK-MB values were greater at 15 min and 24 h post bench press exercise (p < 0.05). No differences were found in lipid peroxidation or α-actin. Interestingly, IL10 values were greater in response to the press bench at 24 h post-test (p < 0.05). Our results suggest that, at equivalent workloads, an arm-based exercise induced higher anti-inflammatory effects and more severe muscle damage compared with a leg-based exercise.